294 Evaluation of production efficiencies among lactating beef and dairy crossbred suckler cows of diverse genetic merit. (7th December 2018) - McCabe, S; McHugh, N; O'Connell, N; Prendiville, R
Abstract: Profitable suckler beef enterprises in Ireland should consist of cows capable of producing adequate milk yield to wean a heavy calf from seasonal low-input pasture based systems. The aim of this study was to determine estimates of grass dry matter intake (GDMI) at pasture and compare production efficiency of lactating beef (n=62) and dairy x beef (DBX; n=69) suckler cows of high and low genetic merit for Replacement Index. A total of 112 primiparous and 80 second parity cows were available from Limousin (LM) or Aberdeen Angus (AA) sires, calved in spring 2014 and 2015 with a mean calving date of 22 March. Cows were managed under a rotational grazing system with average pre- and post- grazing heights of 11.1 (s.d. 2.1) cm and 4.2 (s.d. 0.7) cm respectively. Cow live weight (LW) and body condition score (BCS) were recorded every three weeks. Estimates of milk yield were measured at 120 and 156 days in milk (DIM) in 2014 and at 50, 117 and 184 DIM in 2015 using the weigh-suckle-weigh technique. Estimates of GDMI were established using the n-alkane technique six days post milk yield measures. Beef cows were 55 kg heavier (P<0.001) and had a 0.31 greater BCS (P<0.001) than DBX. The DBX had a 0.8 kg greater GDMI (P<0.001) and produced 1.8 kg more milk than beef (P<0.001). Beef cows had a lower RFI than DBX (0.63 and 0.1 UFL, respectively; P<0.001). The DBX produced 0.45 kg (P<0.001) and 0.12 kg (P<0.001) more milk per unit LW and per unit GDMI, respectively, than beef. Intake capacity was 2.32 and 1.96 kg per unit LW (P<0.001) for DBX and beef, respectively. Low genetic merit cows were 23 kg heavier than high genetic merit cows (P<0.05) but no differences were observed in any of the production efficiency variables investigated.